Pengaruh Tingkat Hutang Perusahaan, Profitabilitas, dan Ukuran Perusahaan terhadap Tarif Pajak Efektif pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia: (Studi Kasus Perusahaan Manufaktur Sektor Non Cyclical yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023) - Mutia Apriliani,; Cris Kuntadi,; Maidani Maidani, (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This study aims to obtain empirical evidence about the effect of Debt Level, Profitability and Company Size on Effective Tax Rates. The independent variables used are debt level, profitability and company size. The dependent variable used is the effective tax rate. This research method uses quantitative research methods. The population in this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2020-2022 period. The sample used used purposive sampling method and resulted in 105 processed data samples that met the criteria. The analysis method used is descriptive statistical test, classical assumption test, multiple regression test, and hypothesis testing. The results showed that partially the level of debt and company size had a positive effect on the effective tax rate, while profitability had no effect on the effective tax rate. Partially the level of debt, profitability and company size affect the effective tax rate.